PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN SIKAP ILMIAH SISWA PADA PEMBELAJARAN IPA DI MTs.S AR-RAUDHATUL HASANAH 2 LUMUT - Edysyah Putra (JURNAL EDUGENESIS, 2019)
This study aims to describe students’ scientific attitude through scientific approach at the eighth grade students of MTs. S. Ar- Raudhatul Hasanah 2 Lumut in 2017/2018 academic year. The research was conducted by using Class Action Research (CAR) for 3 months (April – June 2018) with 28 students as the sample. The research consists of two cycles. The first cycle, (1) the first meeting showed: (a) curiosity attitude was 14.3% (4 students) and (b) team work attitude was 35.7% (10 students) and (2) the second meeting showed: (a) attitude was 39.3% (11 students) and (b) team work attitude was 50% (14 students). The second cycle, the first meeting showed: (a) curiosity attitude was 75% (21 students) and (b) team work attitude was 82.1% (28 students). The research showed scientific approach can increase students’ scientific attitude.